The Performance of Palestinian Local Governments : An Assessment of Service Delivery Outcomes and Performance Drivers in West Bank and Gaza - World Bank (Washington, DC, 2017)
Palestinian local governments represent a key pillar of the future Palestinian state. Predating the Palestinian Authority, many have long and proud histories, including some of the oldest inhabited cities in the world. With increasing political and geographical fragmentation over the last two decades, Local Government Units (LGUs) have become of paramount importance regarding the provision of services to the local population, particularly in areas where the relatively young central government is politically, geographically, and fiscally constrained. Some existing LGUs were created as early as the second half of the 19th century, and over the decades, they have performed under the complexities of disparate political and legal regimes. As the lowest level of governance, Palestinian local authorities fulfill a critical role, not only as a key public service provider but also as the government tier closest to citizens, with elected councils critical for representation and accountability to citizens. The most recent local elections were on May 13, 3017, and in October 2012, only in the West Bank; following the most recent local elections in both the West Bank and Gaza in 2006. Strengthening LGUs and enabling them to perform as fully functional local governments accountable to citizens are key priorities for the Palestinian Authority.